Validation of revisited self-directed learning readiness scale for nursing education among Iranian nursing and midwifery students - Maryam Fooladvand; Mohammad Ali Nadi (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Self-directed learning readiness scale for nursing education (SDLRSNE) was first edited in Fisher and King Learning, which was an alternative for self-directed learning readiness. OBJECTIVES: The present research aims at reinvestigating the subscale factor structure of this tool and present evidence regarding its validity and reliability. METHODS: In this cross-psychometric study, 379 students completed SDLRSNE, with 29 items and three subscales that were selected by conducting simple random sampling method, from among 1135 nursing and midwifery students at Islamic Azad University of Isfahan (Khorasgan), in 2015-2016 academic years. The data were analyzed using SPSS20 and Lisrel8.5 Software. The mentioned data were studied by utilizing descriptive standards and inferential tests such as Cronbach's alpha coefficients, Spearman-Brown, Gutmann, and confirmatory factor analysis (CFA). RESULTS: According to the proper fitness indicators, CFA of 29 items clearly distinguishes self-directing into three elements, including self-management, desire for learning, and self-control. Results demonstrated that all three scale elements have high internal consistency coefficients. CONCLUSION: Results exhibit that short-form scale for self-directed readiness in Fisher and King learning is a valid and reliable tool for identifying the capabilities of the nursing and midwifery student's self-learning.